The art of the SNL portrait - Matthews, Mary Ellen; Michaels, Lorne, 1944-; Castle, Alison; Oberman, Emily (Abrams, 2025)
"The electric spirit of Saturday Night Live as captured by longtime resident photographer Mary Ellen Matthews. Andy Samberg in a giant martini glass. Billie Eilish peeking out of a pile of snow. Kevin Hart writing his own cue cards. Paul Rudd as Paul McCartney. Sarah Silverman dusting the NBC marquee. Alec Baldwin as the Godfather. These are just a few examples of Matthews's bold, dynamic, and playful celebrity portraits that for over two decades have artfully highlighted the hosts and musical guests who help bring the show to life. Week after week, photographer Mary Ellen Matthews makes magic happen on Saturday Night Live with her inventive, irreverent, and truly original photography for the "bumpers"--portraits of the host or musical guest that transition the show to and from commercial breaks. Published on the occasion of the 50th anniversary of SNL and exquisitely designed by Pentagram, this book is the first collection of Mary Ellen's remarkable body of work as well as a celebration of America's longest-running comedy TV show."--Amazon.com.